SISTEM PENERIMAAN KAS ATAS PENDAPATAN KLAIM BPJS DAN NON BPJS PADA RSUD A. MAKKASAU KOTA PAREPARE - Fatimah, Fatimah; Achmar, Muhammad Nuzul (Economos : Jurnal Ekonomi dan Bisnis, 2020)
The aims of this research to determine the system of cash receipts on BPJS and non-BPJS claim income and to know the comparison of cash receipts on income on BPJS and non BPJS claims at RSUD A. Makkasau, Parepare City. The data collection techniques in this study are observation, interviews, and documentation. Data analysis techniques used by researchers are qualitative descriptive analysis techniques, quantitative descriptive, and comparative. The results of the researchers' conclusions on the part of the cash receipts system for claim income of BPJS and Non BPJS at Andi Makkasau Regional Hospital of Parepare are already good and the level of comparison between claim income of BPJS and Non BPJS is 72%.